POLÍTICAS DE LA SUBJETIVIDAD: LAS TÉCNICAS DE SÍ EN EL MUNDO CONTEMPORÁNEO. - Zamora García, Javier; Escámez Navas, Sebastián (Andamios)
The article analyzes how proposals such as personal branding, entrepreneurship, and coaching influence the inner life of people in the West. It highlights the importance of Michel Foucault's techniques of the self to understand the relationship between citizenship and the polis, examining different modes of subjectivation in today's society. The influence of neoliberalism on contemporary subjectivity is mentioned, and approaches to understanding it are explored, including the relevance of new materialisms in the analysis of governmentality. An interview with Nikolas Rose is also presented, known for his work in the social and political history of sciences and the genealogy of subjectivity.